How do safety warnings on medicines affect prescribing?. Issue 10 (3rd October 2022) - Mintzes, Barbara; Reynolds, Ellen; Bahri, Priya; Perry, Lucy T; Bhasale, Alice L; Morrow, Richard L; Dormuth, Colin R
ABSTRACT: Introduction: Many adverse effects of medicines only become known after approval, prompting regulatory agencies to issue post-market safety advisories to support safer care. Our team evaluated advisories issued by national regulators in Australia, Canada, Denmark, the United Kingdom, and the United States from 2007 to 2016 inclusive, comparing regulators' decisions to warn, effects on prescribing, doctors' awareness and responses to warnings, relevant regulatory policies, and specific case studies. Areas Covered: Based mainly on our research program and a narrative review, this commentary describes how often regulators issue safety advisories and effects on clinical practice. We found extensive differences in decisions to warn, timing and content of warnings. Monitoring advice is often inadequate. The most systematic estimate suggests an average reduction in prescribing of around 6% compared with settings with no advisory. Interviews with doctors suggest limited awareness, uptake, and at times belief in these warnings. Expert Opinion: Post-market safety advisories are an important intervention aiming to improve prescribing and use of medicines. However, differing warnings mean that some patients may be exposed to riskier prescribing than others. Better integration of safety information into clinical practice is needed, as well as improved transparency, independence, and public engagement in regulatory decision-making.